The Development of a Suburban City in the Midst of the Boreal Forest: Thompson, Manitoba, Canada, 1956–1970 - Stott, Greg (Urban History Review / Revue d'histoire urbaine, 2017)
Thompson, Manitoba, was established in the late 1950s as both a mining community and a service centre for the north. A collaborative project between provincial officials and the International Nickel Company of Canada (INCO), Thompson borrowed heavily from post–Second World War trends in urban and suburban planning and development while grafting these ideas onto the realities of the boreal forest. At the same time, this orderly design was heavily influenced by the area’s First Nations and the newly arrived inhabitants who came from across Canada and much of the world. While not always a seamless or harmonious process, the interactions and agency of these various players shaped Thompson as a centre for mining and services, as well as a diverse and complex community bridging southern trends and northern realities.